PENGARUH METODE INDEX CARD MATCH TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN FIQIH KELAS VIII MTs MAMBA’UL HUDA TEGALSARI TAHUN AJARAN 2021/2022 - Imam Mashuri; Moh. Erlangga; Raudhotul Inayah (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2022)
The use of modern learning methods is still rarely applied in the learning process that has been going on. This has resulted in the learning achievements of students in recent years not increasing or only experiencing a slight increase in learning achievement. Based on this problem, there needs to be a change in terms of delivering fiqh material so that student learning achievements are increasing which can increase the quality of students in terms of understanding the material. The type of research used in this study is quantitative research. The population in this study was all students of class VIII MTs Mamba'ul Huda Tegalsari while the samples in this study were class 8.1 as a control class and class 8.2 as an experimental class. Based on the results of the study, it shows that the results of the T-test t_ (count )-6,111 > t_tabel 170,814 with a tiled sig of 0.00 < 0.05, which means that H_a accepted and H_0 rejected. Meanwhile, how much influence it has can be seen in the calculation of the value (cohen's effect size) shows that the percentage of 89%, where the number of percentages of 89% that have an effect size value of 1.2 can be interpreted as the application of the Index Card Match method has a high influence. Keywords: Metode Index Card Match, Prestasi Belajar Siswa